Toll-like receptor 4 promotes proliferation and apoptosis resistance in human papillomavirus–related cervical cancer cells through the Toll-like receptor 4/nuclear factor-κB pathway - Ninghong Jiang; Feng Xie; Qisang Guo; Ming-Qing Li; Jingjing Xiao; Long Sui (Tumor Biology)
Toll-like receptor 4 is overexpressed in various tumors, including cervical carcinoma. However, the role of Toll-like receptor 4 in cervical cancer remains controversial, and the underlying mechanisms are largely elusive. Therefore, Toll-like receptor 4 in cervical cancer and related mechanisms were investigated in this study. Quantitative reverse transcription polymerase chain reaction and western blot analyses were used to detect messenger RNA and protein levels in HeLa, Caski, and C33A cells with different treatments. Proliferation was quantified using Cell Counting Kit-8. Cell cycle distribution and apoptosis were assessed by flow cytometry. Higher levels of Toll-like receptor 4 expression were found in human papillomavirus–positive cells compared to human papillomavirus–negative cells. Proliferation of HeLa and Caski cells was promoted in lipopolysaccharide-stimulated groups but suppressed in short hairpin RNA–transfected groups. Apoptosis rates were lower in lipopolysaccharide-stimulated groups relative to short hairpin RNA–transfected groups. In addition, G2-phase distribution was enhanced when Toll-like receptor 4 was downregulated. Moreover, the pNF-κBp65 level was positively correlated with the Toll-like receptor 4 level in HeLa and Caski cells, though when an nuclear factor-κB inhibitor was applied to lipopolysaccharide-stimulated groups, the patterns of proliferation and apoptosis were opposite to those of the lipopolysaccharide-stimulated groups without inhibitor treatment. In conclusion, these data suggest that Toll-like receptor 4 promotes proliferation and apoptosis resistance in human papillomavirus–related cervical cancer cells at least in part through the Toll-like receptor 4/nuclear factor-κB pathway, which may be correlated with the occurrence and development of cervical carcinoma.